BUDAYA KERJA APARATUR SIPIL NEGARA DI KABUPATEN JENEPONTO - Syam, Syamsul Marlin; Rahmiati, Rahmiati; Larissa, Dea (Prodi Hukum Tata Negara (Siyasah Syariyyah) Fakultas Syariah dan Hukum UIN Alauddin Makassar, 2023)
The performance of the State Civil Apparatus has always been a hot topic and is often considered to ignore work culture. This study aims to analyze the work culture of the State Civil Apparatus in Jeneponto Regency, especially in the Population and Civil Registration Office. The type of research used is qualitative research (field research), data sources in the form of primary and secondary data obtained through observation, interviews, documentation and literature studies, in answering these problems, the author uses a syar'i normative approach and an empirical juridical approach. The results showed that work culture in local government agencies is a key instrument in improving the quality of public services. The work culture of the State Civil Apparatus of the Jeneponto Regency Population and Civil Registration Office is strongly influenced by several variables, including leadership behavior, employee selection, organizational culture, learning process and work motivation. Work culture is time to become a system of values, perceptions, behaviors and beliefs held by each State Civil Apparatus to achieve the goals of government organization.